Social Insurance and Health - Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2017)
This chapter reviews the existing empirical evidence on how social insurance affects health. Social insurance encompasses programs primarily designed to insure against health risks, such as health insurance, sick leave insurance, accident insurance, long-term care insurance and disability insurance; and programs that insure against other risks, such as unemployment insurance, pension insurance and country-specific social insurance. These insurance systems exist in almost all developed countries around the world. This chapter discusses the state-of-the art evidence on each of these social insurance systems, briefly reviews the empirical methods for identifying causal effects, and examines possible limitations to these methods. The findings reveal robust and rich evidence on first-stage behavioral responses ("moral hazard") to changes in insurance coverage. Surprisingly, evidence on how changes in coverage impact beneficiaries' health is scant and inconclusive. This lack of identified causal health effects is directly related to limitations on how human health is typically measured, limitations on the empirical approaches and a paucity of administrative panel data spanning long-time horizons. Future research must be conducted to fill these gaps. Of particular importance is evidence on how these social insurance systems interact and affect human health over the lifecycle and in the long-run.
Keywords: H1; H5; I1; J2; 330; social insurance; health; causal effects; microeconometrics; reduced-form methods; structural methods